A model for infectious disease control (Colombia Medica, 1987)
A theoretical model for the control of infectious diseases is presented. Keeping the size of the reservoir at a minimum, avoiding the entrance of the infectious agent into the environment, interrupting transmission, avoiding the entrance of the agent into the new host, improving the resistance of the new host, and modifying the whole environment are the six strategies considered. For each one of the activities, proper examples are developed, and the combination of the strategies is also exemplified.The main objective is to apply the model to the epidemiological training of medical and postgraduate students in public health and epidemiology. Still, the model is also important for the cost-benefit appraisal of public health interventions.